Pendekatan Andragogi dalam Pengajian Sosialita Kota Langsa - Mukhlis Rais (At-Tafkir, 2021)
This article discusses the andragogy approach process carried out by the presenter Ustadz when filling out the recitation of socialite mothers who are active in the Taklim Amanah Council and the Taklim Hidayatullah Council, Langsa City, the obstacles when filling out the recitation, and the implications for their social and religious activities in Langsa City. The number of taklim assemblies recorded in the list of recapitulation of the Office of Islamic Shari'a and Dayah Education in Langsa City is 195 taklim assemblies. Officially, these two taklim assemblies have not been included in the list compiled by the Office of the Office of Islamic Shari'a and Dayah Education in Langsa City. However, the recitation activities of the two taklim councils are quite unique. In addition, the congregation is dominated by socialite mothers with a variety of religious materials and full social activities in a week. After carrying out the process of gathering information through in-depth interviews with Ustadz at the Amanah and Hidayatullah Taklim Council and through observation of assistance and participants, this study found that the andragogy approach process in these two taklim assemblies was very special, namely using a dialogical approach, psychological, and religious as contained in the concepts and principles of the andragogy approach. So that the implication in social and religious activities is that the socialites of Langsa City are able to provide positive benefits for people's lives.